Effects of Sea Animal Activities on Tundra Soil Denitrification and nirS‐ and nirK-Encoding Denitrifier Community in Maritime Antarctica - Dai, Hai-Tao; Zhu, Ren-Bin; Sun, Bo-Wen; Che, Chen-Shuai; Hou, Li-Jun (Frontiers in Microbiology, 2020)
In maritime Antarctica, sea animals, such as penguins or seals, provide a large amount of external nitrogen input into tundra soils, which greatly impact nitrogen cycle in tundra ecosystems. Denitrification, which is closely related with the denitrifiers, is a key step in nitrogen cycle. However, effects of sea animal activities on tundra soil denitrification and denitrifier community structures still have received little attention. Here, the abundance, activity, and diversity of nirS‐ and nirK-encoding denitrifiers were investigated in penguin and seal colonies, and animal-lacking tundra in maritime Antarctica. Sea animal activities increased the abundances of nirS and nirK genes, and the abundances of nirS genes were significantly higher than those of nirK genes (p < 0.05) in all tundra soils. Soil denitrification rates were significantly higher (p < 0.05) in animal colonies than in animal-lacking tundra, and they were significantly positively correlated (p < 0.05) with nirS gene abundances instead of nirK gene abundances, indicating that nirS-encoding denitrifiers dominated the denitrification in tundra soils. The diversity of nirS-encoding denitrifiers was higher in animal colonies than in animal-lacking tundra, but the diversity of nirK-encoding denitrifiers was lower. Both the compositions of nirS‐ and nirK-encoding denitrifiers were similar in penguin or seal colony soils. Canonical correspondence analysis indicated that the community structures of nirS‐ and nirK-encoding denitrifiers were closely related to tundra soil biogeochemical processes associated with penguin or seal activities: the supply of nitrate and ammonium from penguin guano or seal excreta, and low C:N ratios. In addition, the animal activity-induced vegetation presence or absence had an important effect on tundra soil denitrifier activities and nirK-encoding denitrifier diversities. This study significantly enhanced our understanding of the compositions and dynamics of denitrifier community in tundra ecosystems of maritime Antarctica.